Exoskeleton for Biofunctionality Protection of Enzymes and Proteins for Intracellular Delivery. Issue 1 (26th October 2020) - Dutta, Saikat
Abstract : Driven by the challenges to protect and restore biofunctionality of enzymes and proteins due to fluctuation of temperature, pH, and solvents, desired tolerances against the intracellular microenvironment can be gained via sheltering enzyme and proteins into nanoscale cages of exoskeleton, one of which involves confinement into the pore and channels of metal–organic frameworks (MOFs). While confining biomolecules, such framework exoskeleton and nanoscale cages should drive the enzyme embedding process and induce the formation of the resulting biocomposite suitable for intracellular delivery for therapeutic applications. Translational challenges faced by framework materials such as ZIF‐8 exoskeleton along with few more MOFs for armoring biofunctionality modulation of enzymes and proteins for intracellular delivery efficiency are highlighted. Herein, enzyme embedding patterns, encapsulation of oxidase enzymes, hybrid protein–MOFs, protected protein delivery, and mechanism of biofunctionality protection are discussed. Furthermore, an attempt is made to highlight the scope of exoskeleton biocomposites. Abstract : The scope of using exoskeleton protected enzymes and proteins are emphasized wherein desired tolerances against the intracellular microenvironment can be gained via sheltering enzyme and proteins into nanoscale cages of metal‐organic frameworks (MOFs) and polymers with the mechanism of biofunctionality protection. The intracellular activity of hybrid protein‐MOFs for protein delivery brings the major focus on the exoskeleton.